Ecologia das populações e comunidades dos camarôes Decapoda no litoral norte de Santa Catarina - Wolf, Milena Regina [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Due to the impact caused by anthropic action on marine environment, the purpose of this work was to provide subsidies for species conservation at Babitonga Bay adjecent area in the state of Santa Catarina, Brazil. The aim was to catalogue existing species of marine shrimps communities, to detect and to describe general patterns in its temporal-spatial distribution and the relation to environmental variables that characterize its habitat. Therefore, ecological indexes were measured and environmental to biological parameters were tested with multivariate analysis. A shrimp boat equipped with double-rig nets was used and it travelled five parallel to the coast with a depth of stations 5, 8, 11, 14 e 17 m. The total richness reached twelve species, belonging to three superfamilies, six families and eleven genera. Of these, six species of peneid shrimps are marketed: Xiphopenaeus kroyeri, Artemesia longinaris, Pleoticus muelleri, Farfantepenaeus brasiliensis, Farfantepenaeus paulensis and Litopenaeus schmitti. The other species of peneids Rimapenaeus constrictus and Sicyonia dorsalis, and caridean shrimps Exhippolysmata oplophoroides, Alpheus intrinsecus, Nematopalaemon schmitti and Periclimenes paivai belong to bycatch of fisheries resources. X. kroyeri was a dominant (D) species in space and time, presenting discrepant values of relative abundance 97.7% when compared with the second most abundant species P. muelleri 1.1%, a circumstance that directly influenced the results of cluster analysis, the diversity (H’) and eveness (J’) values, which were high when the abundance of the species was lower. The patterns of the marine shrimp communities investigated in other regions were corroborated by the result of this study. Changes in shrimp communities could be related to variations in measured environmental variables and biological requirements specific to each species. The bottom temperature and sediment grain size were the preponderant ...

Frente aos impactos causados pela ação antrópica no ambiente marinho, a proposta desse trabalho foi fornecer subsídios para a conservação das espécies, na área adjacente à Baía da Babitonga, estado de Santa Catarina, Brasil. O objetivo foi inventariar as espécies existentes da comunidade de camarões marinhos, detectar e descrever padrões gerais na sua distribuição espaço-temporal e relação às variáveis ambientais que caracterizam seu habitat. Portanto, foram mensurados os índices ecológicos e testados os parâmetros ambientais aos biológicos com análise multivariada. Os camarões foram coletados em julho de 2010 a junho de 2011, junto às variáveis ambientais, como temperatura e salinidade da água e textura e conteúdo de matéria orgânica do sedimento. Utilizou-se um barco camaroneiro equipado com redes double-rig, o qual percorreu cinco pontos paralelos a costeira com profundidades de 5, 8, 11, 14 e 17 m. A riqueza total chegou a doze espécies, pertencendo a três superfamílias, seis famílias e onze gêneros. Dessas, seis espécies de camarões peneídeos são comercializados: Xiphopenaeus kroyeri, Artemesia longinaris, Pleoticus muelleri, Farfantepenaeus brasiliensis, Farfantepenaeus paulensis e Litopenaeus schmitti. As demais espécies de peneídeos, Rimapenaeus constrictus e Sicyonia dorsalis, e carídeos, Exhippolysmata oplophoroides, Alpheus intrinsecus, Nematopalaemon schmitti e Periclimenes paivai, pertencem à fauna acompanhante dos recursos pescados. X. kroyeri foi a espécie dominante (D) espacialmente e temporalmente, apresentando valores discrepantes de abundância relativa 97,7% quando comparada à segunda espécie de maior abundância P. muelleri (1,1%), circunstância que influenciou diretamente nos resultados das análises de agrupamento e nos valores de diversidade (H’) e equitabilidade (J’), que foram altos quando a abundância da espécie foi menor. Esse resultado corroborou aos padrões das ...
Keywords: Pesca de arrastão; Camarão - Reprodução; Levantamentos ecologicos; Trawls and trawling